Pulmonary Capillary Hemorrhage Induced by Acoustic Radiation Force Impulse Shear Wave Elastography in Ventilated Rats. (31st January 2019) - Miller, Douglas L.; Dong, Zhihong; Dou, Chunyan; Patterson, Brandon; Raghavendran, Krishnan
Abstract : Objectives: Diagnostic ultrasound (DUS) imaging can induce pulmonary capillary hemorrhage (PCH), possibly related to the ultrasonic radiation surface pressure arising from reflection at the lung blood‐air interfaces. Acoustic radiation force impulse (ARFI) elastography is a relatively new DUS mode with high‐energy "push pulses" used to move tissue and generate shear waves. The objective of this study was to characterize PCH induced by the ARFI elastographic mode for comparison with other previously tested DUS modes. Methods: Pulmonary capillary hemorrhage induction was examined for ARFI elastographic frames with 5.7‐MHz push pulses (Acuson S3000; Siemens Medical Solutions, Mountain View, CA), which had a derated PRPA of 2.6 MPa. Groups of rats with tracheal tube placement had no ventilation (spontaneous breathing), intermittent positive pressure ventilation (IPPV), or IPPV plus 8 cm H2 O of positive end‐expiratory pressure (PEEP). Exposure was to 1 or 20 manually triggered image frame acquisitions. The PCH area was measured on the lung surface. Results: All 20‐frame exposure groups, and even the single‐frame group, had significant PCH relative to shams. Single‐frame exposures produced significantly less PCH ( P  = .002) than 20‐frame exposures in rats with a tracheal tube only (spontaneous breathing). The PEEP inhibited the PCH and produced about half of the PCH area induced for IPPV without PEEP ( P  = .014). Conclusions: The PCH results were comparable with those from a previous study using B‐mode or color Doppler exposure for 5 minutes; however, these modes delivered many more pulses for continuous imaging frames, suggesting that the ARFI elastographic frames were individually much more effective.